Profiling of Phytochemical Compounds of East Java Red Rice Bran Has the High-Value Biological Activities as Antioxidant and Antidiabetic - Yoravika Dwiwibangga; Anna Safitri; Fatchiyah Fatchiyah (Indonesian Journal of Chemistry, 2022)
The phytochemicals contained in rice bran, mainly flavonoid compounds, are predicted to have biological activity. Flavonoids are able to counteract the free radicals and degrade insulin resistance. The East Java Red Rice Bran samples, e.g., Mentik Wangi, Aek Sibundong, and Blambangan, were used in the study. Their phytochemical profiles, functional groups, antioxidant, and antidiabetic activities were investigated. The phytochemical analysis showed that the bran of Mentik Wangi, Aek Sibundong, and Blambangan contained flavonoid, triterpenoid, phenolic, tannin, and glycoside. Based on the FTIR, some functional groups were identified in three rice bran varieties, namely, the O-H stretching, C-H aliphatic, C-H sp3 stretching, C=C stretching aromatics, C=C stretching alkenes, CH2 and CH3 bonds rocking, C-H aromatic, CH-OH stretching alcohols, and C-O stretching ether or ester suggesting that rice brans are rich in phytochemical compounds. Through LC-HRMS analysis in positive ion mode, several types of flavonoids were confirmed. Pinocembrin was found in the three brands. The highest antioxidant and antidiabetic activity were observed in Blambangan rice bran with an IC50 value of 1.09 and 75.76 µg/mL, respectively. To conclude, the red rice bran phytochemical compounds exhibit potential biological activities as antioxidant and antidiabetic agents.